Nieve Artificial en el Perú: Análisis de Riesgos Ambientales y Sociales de su Implementación en Zonas Naturales - Sanchez Contreras, Gustavo Adolfo; Gonzales García, Carlos Marcelo; Guerra Palomino, Adriana; Valderrama Martel, Génesis Ariana; Cabrera Mostacero, María José (LACCEI, 2025)
This research paper, entitled "Artificial Snow in Peru: Analysis of Environmental and Social Risks of its Implementation in Natural Areas," proposes a critical assessment of the implications of implementing artificial snow in natural ecosystems in Peru, particularly in high Andean regions. The increase in tourist demand in areas where snow is rare has promoted the use of artificial technologies to simulate winter conditions, with the resulting environmental and social consequences. Consequently, a comprehensive analysis is required that meets scientific and technical criteria from a multidisciplinary perspective. A thorough analysis also aims to assess the potential impacts on water resources, biodiversity, and ecological balance; the social impacts on local communities, including displacement, changes in traditional economic activities, and conflicts over water use; and the available environmental management tools and their level of application in this type of project. The study concludes that the implementation of artificial snow, when carried out without an adequate environmental assessment and without the participation of local populations, has irreversible ecological and social effects. For this reason, environmental control mechanisms must be strengthened, a sustainability approach implemented, and tourism alternatives promoted that are compatible with the preservation of the natural environment and respect for Andean communities.